Customer perceived satisfaction among foreign broadband user of Maxis Communication Berhad / Ahmira Aznin Ahmad - Ahmad, Ahmira Aznin (Faculty of Business and Management, 2010)
Customer satisfaction means the intention to make future purchases, it is assumed that high levels of attitudinal loyalty are an outcome of high levels of satisfaction. Satisfaction is defined as an emotional post-consumption response that may occur the result of comparing expected and actual performance or it can be an outcome that occurs without comparing expectations. Satisfaction also leads to attitudinal loyalty. In this research, product and services, coverage, speed and customer service is the factors that can influence customer satisfaction in choosing Maxis to be their chosen broadband provider. Those factors also have been identified in order to investigate whether or no those factors have significant relationship with foreign customer satisfaction towards Maxis Broadband. The survey conducted at the Maxis Berhad. The sample size for this study is 50 respondents who are all foreigners. Data obtain using two methods that are primary and secondary data. Respondents are required to answer the questionnaire that include the statement regarding relationship between factors and customer perceived satisfaction towards Maxis broadband, Once the necessary data has been collected, the data will be analyzed and summarize in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 14.0 has been used to summarize the data. The results are in the form of reliability testing, frequency and regression analysis. Based on this research, the result indicates that there are significant relationship between all the factors and customer perceived satisfaction which includes product and services, coverage, speed and customer service. In additional, based on the mean and standard deviation for each factor, the first rank that gives the highest significant level according to their relationship with customer